Komparasi Metode Peramalan Dalam Meramalkan Permintaan Layanan Wajib Pajak - Putrananda, Aldy Prasetyo; Siagian, Bekman (JATISI, 2025)
Through the effectiveness and efficiency in carrying out its service functions, Directorate General of Taxes (DGT) can enhance taxpayer satisfaction, which in turn will encourage increased taxpayer compliance. The growth in the number of registered taxpayers, accompanied by an increase in the demand for tax services, underscores the urgency for DGT to develop strategies for forecasting the future demand of tax services. This will ensure that DGT can maintain a high level of taxpayer satisfaction. However, no single forecasting method can be universally applied to all conditions. Therefore, this study aims to identify forecasting methods that can be utilized by DGT to predict future demand for tax services. Among several forecasting methods tested in this study, including gradient boosting, naïve level, naïve seasonal, and Holt-Winters, Holt-Winters Additive method was found to be the most suitable. This method yielded RMSE of 30.518,451 ± 8.015,402, MAE of 24.691,949 ± 3.048,462 and MAPE of 8,16% ±1,76%.